THE VALUE OF LOCAL WISDOM IN THE ECONOMIC PRACTICE OF THE BANJAR COMMUNITY IN BANJARMASIN - Delva Yuliana; Bambang Subiyakto; Deasy Arisanty (Universitas Lambung Mangkurat, 2026)
This research aims to examine the values of local wisdom, especially honesty and respect for customs, in the economic transactions of the Banjar community in Banjarmasin, South Kalimantan. Local wisdom plays an important role in social and economic interactions. Honesty is considered the main value that builds trust in every economic transaction, while respect for custom serves as a social norm that regulates economic behavior and strengthens societal cohesion. With a qualitative approach through in-depth interviews, observation, and documentation, it was found that honesty is very important in maintaining social and economic stability, building networks of trust, and reducing conflict. Economic actors in Banjarmasin uphold honesty as social capital that binds the relationship between traders and consumers. Respect for customs also influences the way the Banjar people conduct transactions, creating harmony within the community. These values are starting to change due to the influence of modernization and globalization, which are more oriented towards short-term profits. This research emphasizes the importance of preserving local wisdom to maintain the sustainability of economic transactions based on honesty and respect for customs in Banjar society.